Antimicrobial resistance and pirAB-like profiles of Vibrio parahaemolyticus in Pacific white shrimp - Rortana, Chea; Wajjwalku, Worawidh; Boonyawiwat, Visanu; Hrianpreecha, Charuwan; Thongratsakul, Sukanya; Amavisit, Patamabhorn (Agriculture and Natural Resources, 2018)
Antimicrobial susceptibility, plasmid-mediated quinolone resistance (PMQR) genes, the pirAB-like virulent gene and DNA gyrase A (gyrA) subtyping were studied to update the virulent profiles of Vibrio parahaemolyticus isolated from Pacific white shrimp (Litopenaeus vannamei) and pond water of shrimp farms. Sixty-six isolates were obtained from seven provinces in Thailand. Disc diffusion assay revealed the following antimicrobial resistant rates: ampicillin, 98.48%; doxycycline, 3.03%; oxytetracycline, 4.55%; erythromycin, 6.06%; florfenicol, 1.52%; and trimethoprim/sulfamethoxazole, 1.52%. The isolates were not resistant to quinolone agents (ciprofloxacin, enrofloxacin, norfloxacin, ofloxacin). Nine PMQR genes were screened in the isolates that presented quinolone intermediate susceptibility. Only the qnrVC quinoloneresistant gene was found in one multidrug-resistant (MDR) isolate that was collected from the pond water. Of all isolates, 39.39% carried the pirAB-like gene, which causes acute hepatopancreatic necrosis disease in shrimp. All pirAB positive isolates were collected from the shrimp samples but not from the water. Based on the gyrA sequence subtyping, the isolates were classified into five types. The isolates that carried the pirAB-like virulent gene were of three different types, whereas the MDR isolates were of the same type. There was no association between the pirAB and resistant profiles. Though V. parahaemolyticus in this study presented low antimicrobial resistance rates, the few isolates that presented MDR profiles and their capabilities to acquire a plasmid resistant gene indicate the risk of AMR dissemination in the environment.